Consummatory Taste Reward in Obesity - Simon, Jonathan B; Abdeen, Ghalia N; Miras, Alexander D; le Roux, Carel W. (Journal of Nutritional Therapeutics, 2012)
Obesity is a disease of multiple origins and results from the interaction between the genetic predisposition of a person and environmental factors, including food preferences. Even though the literature is not always consistent, there is strong support for the notion that the obese do not just consume more calories, but also prefer calorifically dense foods. In this review, the evidence for differences in the consummatory reward of taste, and in particular sweet and fat taste, will be examined in the context of food preferences in obesity.